Comparing the effects of laparoscopic radical surgery and traditional open surgery on short-term efficacy and long-term survival in patients with colorectal cancer - Lin, Yanhong; Ling, Jie; Liao, Chuting; Wang, Xiangjun; Yin, Junfeng (Frontiers in Surgery, 2026)
AimThis study aimed to compare the impacts of laparoscopic surgery (LS) and open surgery (OS) on the short-term efficacy and long-term survival in patients diagnosed with colorectal cancer (CRC).MethodsSixty CRC patients who underwent LS at our hospital between January 2021 and January 2022 were enrolled as the LS group. Another 60 CRC patients who received OS during the same period at the same hospital were selected as the OS group. The study compared surgical parameters, postoperative recovery metrics, stress response indicators, inflammatory markers, immune function markers, the incidence of postoperative complications, quality of life assessments, and 3-year survival rates between the two cohorts.ResultsThe LS group exhibited a longer surgical duration but had shorter surgical incisions and less intraoperative blood loss compared to the OS group (P < 0.01). The number of lymph nodes dissected was similar in both groups (P > 0.05). The LS group also demonstrated quicker recovery, with shorter times to anal gas expulsion, defecation, oral intake, and activity, as well as a reduced hospital stay (P < 0.01). On the third day post-surgery, the study group showed lower levels of cortisol, epinephrine, and norepinephrine (P < 0.05), along with decreased levels of IL-6, TNF-α, and CRP (P < 0.05). Conversely, the study group had higher levels of CD3+, CD4+, and CD4+/CD8+ on the third day after surgery (P < 0.05). The overall incidence of postoperative complications was lower in the study group (P < 0.05). Twelve months post-surgery, both groups showed significant improvements in the Gastrointestinal Quality of Life Index (GIQLI) scores, with the study group outperforming the OS group (P < 0.05). Kaplan–Meier analysis revealed a 3-year survival rate of 81.67% in the study group vs. 80.00% in the OS group, with no statistically significant difference (P = 0.833).ConclusionLS for CRC patients is highly effective, alleviating inflammatory and immune stress responses in patients, lowering the incidence of postoperative complications, improving the quality of life of patients, and having a long-term efficacy comparable to OS.